Análisis de los factores geográficos, demográficos y socioeconómicos que afectan al consumo de cultura - Paucar Zuloaga, Jean Sebastián (2022)
Research on consumption in culture is a field of study that has only gained some relevance to economists in recent years. The objective of this research is to find the causalities that make individuals consume different types and aspects of culture in the regions of Peru, from January 2017 to December 2019. As variables that represent culture, we have attendance at Archaeological Monuments, Museums, Theater, Dance, Music and traditional festivals; having as explanatory variables the rural and urban environment, age, sex, socioeconomic strata and the budget assigned to each department directed to the cultural sector. Statistical and econometric analysis was performed using the fixed and random effects data panel. As a result, most of the variables are significant in the research models. With this research it can be concluded that the income and socioeconomic stratum in which individuals are located, the state budget directed to the cultural sector, urban areas and in certain circumstances demographic characteristics directly influence cultural consumption. It is recommended to promote the study of Cultural Economy because it has a lot of knowledge to offer, it should also promote studies on the influence of culture in societies.